Fiscal Policy Effect on Stock Market in ASEAN 5 - Jonathan, Brian (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2024)
This research is aimed to investigate the effect of fiscal policy on the stock market in ASEAN 5. This paper takes different approach in building the framework of direct and indirect transmission. Alongside choosing ASEAN 5 as sample with the focus of economic integration and SVAR. The finding are as follow: fiscal policy have positive relation with direct transmission but negative towards stock market. Bond yield is affected positively by fiscal primary balance and has a positive impact on stock market index. Central rates have a negative impact by Primary balance but positive impact towards stock market. Lending rate also reacts negatively towards primary balance and positive towards stock market. And consumption has a negative effect on the stock market index.